THE INFLUENCE OF BLUE OCEAN STRATEGY AND INNOVATION CAPABILITY ON PURCHASING DECISIONS IN THE RUMOH TUHA COFFEE SHOP, LHOKSEUMAWE CITY - Nelly Astria; Cut Sukmawati; Teuku Zulkarnaen; Nanda Ameliany; Sufi (RADJA PUBLIKA, 2025)
The purpose of this study is to examine how Rumoh Tuha Coffee Shop in Lhokseumawe City's customers' decisions are influenced by Blue Ocean Strategy and Innovation Capability. The highly competitive culinary industry serves as the backdrop for this study, which requires companies to offer unique value in orders to attract customers. Questionnaires were distributed to 100 respondents using a simple random sample technique to complete in order to gather primary data for the descriptive quantitative approach. Multiple linear regression was used to analyze the data. The findings show that the Blue Ocean Strategy significantly and favorably influences purchase decisions to some extent. On the other hand, purchasing decisions are significantly impacted by innovation capability. Both factors simultaneously have a favorable and noteworthy impact. These findings indicate that a unique value creation strategy is more appreciated by consumers than innovations that do not align with market preferences. Therefore, implementing an appropriate and targeted strategy is key to driving consumer purchasing decisions.